Peningkatan Kemampuan Manajerial UMKM Sari Kedelai di Sumberrejo Kabupaten Pasuruan - Dwijanto Witjaksono , Andre; Tri Wijayati Wardoyo, Dewie; Rozaq, Khoirur; Nugrohoseno, Dwiarko; Budiono, Budiono; Kusumaningum, Trias Madanika (Abimanyu : Jornal of Community Engagement, 2023)
MSMEs are an important aspect of economic development in Indonesia. However, in its journey, MSMEs still have many limitations so that real action is needed to overcome problems in the field of increasing managerial capabilities and production efficiency. The purpose of this article is to increase managerial capabilities and production efficiency of Soybean MSMEs in Sumberrejo, Pasuruan Regency. The method used is the approach method in the form of assistance in providing MSME training in the village and designing soybean skin peeler production tools. The result of this community service is that partners are able to compile simple financial reports and procedures for online sales using social media and marketplaces so that there is an increase in the managerial capabilities of MSMEs. In addition, the soybean skin peeler production tool is able to increase the effectiveness of MSME production from soybeans.